2015
DOI: 10.1093/ehjcvp/pvv006
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary antithrombotic strategies in patients with acute coronary syndromes managed without revascularization: insights from the EYESHOT study

Abstract: AimsPatients with acute coronary syndromes (ACSs) who are managed without coronary revascularization represent a mixed and understudied population that seems to receive suboptimal pharmacological treatment. Methods and resultsWe assessed patterns of antithrombotic therapies employed during the hospitalization and in-hospital clinical events of medically managed patients with ACS enrolled in the prospective, multicentre, nationwide EYESHOT (EmploYEd antithrombotic therapies in patients with acute coronary Syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
3
11
0
3
Order By: Relevance
“…Barely half of these patients were discharged on DAPT despite their higher GRACE risk score when compared to revascularised patients, closely matching the 54% reported in CRUSADE 2004-2005 [5]. A recent Italian registry study showed that at the time of discharge, DAPT was prescribed in 58.8% of medically managed patients [23].…”
Section: Accepted Manuscriptsupporting
confidence: 66%
“…Barely half of these patients were discharged on DAPT despite their higher GRACE risk score when compared to revascularised patients, closely matching the 54% reported in CRUSADE 2004-2005 [5]. A recent Italian registry study showed that at the time of discharge, DAPT was prescribed in 58.8% of medically managed patients [23].…”
Section: Accepted Manuscriptsupporting
confidence: 66%
“…Although there is mutual agreement on the importance of revascularisation in patients with NSTE-ACS, a large proportion of these patients do not benefit from this treatment. In fact, in the Italian EYESHOT registry 42.7% of patients with NSTE-ACS were started on conservative therapy, of which 17.2% did not even receive coronary angiographic examination, while 25.5% were not revascularised following coronary angiography 236 .…”
Section: Dual Antiplatelet Therapy In Patients With Acute Coronarmentioning
confidence: 99%
“…прак-тически являющихся «неизученными» [5]. В отличие от пациентов, включенных в программу проспективных клинических исследований, риск клинических событий может быть выше в рутинной практике, и персонали-зированная антиагрегантная терапия может играть большую роль.…”
Section: Monitoring Of Antiplatelet Therapy Effectiveness контроль эфunclassified